Analysis of Administrative Services in Accelerating Bureaucratic Reform at the Inspectorate General of the Ministry of Home Affairs - Janet Albertina Dian Kolle; Udaya Madjid; Sutiyo, Sutiyo (Sean Institute, 2025)
This study began with the slow service process, lack of involvement of inspectorate employees, and complicated services. The study aims to analyze the implementation of administrative services in accelerating bureaucratic reform at the Inspectorate General of the Ministry of Home Affairs, identify supporting and inhibiting factors in administrative services in accelerating bureaucratic reform at the Inspectorate General of the Ministry of Home Affairs, This study uses a qualitative research design with descriptive methods and an inductive approach, data collection techniques that have been carried out in this study were carried out by observation, interviews, documentation. The results of the study show that the implementation of administrative services at the Inspectorate General of the Ministry of Home Affairs includes handling complaints, providing recommendations related to the regional inspector selection committee, and issuing a certificate of freedom from findings. This service is carried out through two mechanisms, namely manual and online, with the aim of increasing efficiency and accelerating the administrative process. Supporting factors in administrative services at the Inspectorate General of the Ministry of Home Affairs are the availability of adequate facilities and infrastructure, reliable technology, fast response from officers, guaranteed document security, and employee commitment. Inhibiting factors, namely the absence of procedures (SOP) for officers, officer discipline, uncertainty of service completion time, and system and internet disruptions are still challenges in improving the efficiency and effectiveness of administrative services. Efforts made by the Inspectorate General of the Ministry of Home Affairs through the preparation of SOPs, increasing officer discipline and professionalism, certainty of service completion time, optimizing IT infrastructure, and strengthening periodic supervision and evaluation, the Inspectorate General seeks to create more efficient, transparent, and accountable services.